Preservation Method of Rumen Fluid Collected From Harvested Cattle Alters in vitro Digestibility of Reference Feedstuffs - Garcia, Taylor J.; Cherry, Nichole M.; Guay, Kimberly A.; Brady, Jeffrey A.; Muir, James P.; Smith, William B. (Frontiers in Animal Science, 2021)
The objective of our experiment was to evaluate preservation and revitalization strategies for rumen inoculum anticipating research and veterinary applications. Rumen fluid samples were collected from 12 harvested cattle. Liquid samples were divided into five 500-mL aliquots which were randomly allocated to one of five treatments in a 2 × 2 + 1 augmented factorial design. Factors included preservation method (freezing [FZN] or lyophilization [LYO]) and preservative (glycerol; + or -). A fresh control (CON) was maintained from each sample. Feedstuffs used in this experiment were alfalfa hay, Coastal bermudagrass hay, cracked maize, rice bran, and soybean meal. Reference feedstuffs were subjected to batch culture in vitro true digestibility (IVTD) and in vitro NDF digestibility (IVNDFD) assays using inoculum from each of the five treatments. There was an effect (P < 0.05) of preservation method, preservative, and their interaction for both IVTD and IVNDFD of each of the five references feedstuffs. Freezing or lyophilization of rumen inoculum reduced (P < 0.05) IVTD and IVNDFD of reference feeds relative to the CON. Despite lower degradation of feeds when frozen or lyophilized rumen fluid was used rather than fresh, differences between them in IVTD and IVNDFD suggest that, in the absence of fresh inoculum, preserved rumen fluid may be a viable option for veterinary applications, such as transfaunation, but likely will not be viable for research applications.